2022
DOI: 10.3389/fphar.2022.920855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periplaneta americana extracts on the growth and proliferation of cutaneous interstitial cells in cutaneous-wound healing

Abstract: Cutaneous-wound healing requires a coordinated reaction of multiple cells, including interstitial cells. Impaired recovery of cutaneous wounds can lead to various adverse health outcomes. Kangfuxin (KFX), an extract obtained from Periplaneta americana, is beneficial in cutaneous-wound healing. In this study, we isolated dermal cells from suckling mice and established a mouse model of cutaneous injury to evaluate the therapeutic effects of KFX. Cell biology experiments indicated that treatment with KFX improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The preparation is obtained from the ethanol extract of PA with the main components of polyols and peptides. Over the years, Kangfuxin liquid has been widely used in the treatment of wounds, pressure ulcers, peptic ulcers, oral ulcers, and chronic gingivitis with the characteristics of excellent effectiveness, convenient administration, and no serious adverse reactions [5,129,130]. Xinmailong injection has been applied in the therapy of heart failure (HF) in China, which contains four active ingredients: adenosine, inosine, protocatechuic acid and pyroglutamine dipeptide.…”
Section: Key Issues In Basic Study and Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation is obtained from the ethanol extract of PA with the main components of polyols and peptides. Over the years, Kangfuxin liquid has been widely used in the treatment of wounds, pressure ulcers, peptic ulcers, oral ulcers, and chronic gingivitis with the characteristics of excellent effectiveness, convenient administration, and no serious adverse reactions [5,129,130]. Xinmailong injection has been applied in the therapy of heart failure (HF) in China, which contains four active ingredients: adenosine, inosine, protocatechuic acid and pyroglutamine dipeptide.…”
Section: Key Issues In Basic Study and Drug Developmentmentioning
confidence: 99%
“…In general, their bioactive constituents exhibit stronger pharmacological effects than those of plants. As the famous representative, the insects of the family Blattidae have a long history of medicinal application, and some studies have demonstrated their antitumor [1][2][3], tissue repair [4][5][6], antibacterial [7], antiviral [8], and other pharmacological effects [9,10]. The family Blattidae belongs to Arthropoda, Insecta, Pterygota, Blattariae in entomological taxonomy, which has existed on the earth for 320 million years [11].…”
Section: Introductionmentioning
confidence: 99%
“…Periplaneta americana (PA) is an important medicinal insect, which was first published in Shennong's Classic of Meteria Medica, and has been applied for the treatment of wounds, burns, ulcers, and primary liver cancer (Zeng et al, 2019). In recent years, continuous studies on PA show that the PA extract possesses many biological activities, including anti-tumor (Zhao et al, 2017), wound-healing (Liang et al, 2022), anti-liver fibrosis (Li et al, 2018), and antioxidant (Yang et al, 2022), anti-inflammatory (Lu et al, 2019), and anti-bacterial activity (Ali et al, 2017). Compared with these biological activity researches, the chemical studies on the pharmacodynamic active ingredients in PA lag behind.…”
Section: Introductionmentioning
confidence: 99%